Distribution feeder reconfiguration with distributed generation using backward/forward sweep power flow - grey wolf optimizer - Syed Muhammad Fadli, Syed Drus; Norhafidzah, Mohd Saad; Mohammad Fadhil, Abas; Suliana, Ab Ghani; Norazila, Jaalam; Ali, Abid (Institute of Electrical and Electronics Engineers Inc., 2023)
This article presents an effective combination method based on Backward/Forward Sweep Power Flow- Grey Wolf optimizer (BFSPF-GWO) for feeder reconfiguration in a distribution network with the presence of distributed generation (DG). The 33-bus test system by adding five tie line switches is proposed with the objective functions of minimizing total power losses and improving the voltage profiles. The results reveal a reduction in active and reactive power losses at 71.41% and 67.66%, respectively. The optimal sizing of DG and installation location are identified by installing a 2.26 MW DG at bus 29. The magnitudes of voltage profiles and critical buses in the test system have been improved. The proposed BFSPF-GWO algorithm's performance in DG placement and sizing with feeder reconfiguration has been evaluated by comparing the results with Mixed-integer optimization by GA (MIOGA) and Particle Swarm optimization (PSO).